Measurement of the absolute branching fractions of Lambda(+)(c) -> Lambda eta pi(+) and Sigma(1385) (+) eta - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2019)
We study the decays Lambda(+)(c) -> Lambda eta pi(+) and Sigma(1385)(+)eta based on Lambda(+)(c)(Lambda) over bar (c) pairs produced in e(+)e(-) collisions at a center-of-mass energy of root s = 4.6 GeV, corresponding to an integrated luminosity of 567 pb(-1). The data sample was accumulated with the BESIII detector at the BEPCII collider. The branching fractions are measured to be beta(Lambda(+)(c) -> Lambda eta pi(+)) = (1.84 +/- 0.21 (stat) +/- 0.15(syst))% and B(Lambda(+)(c) -> Sigma(1385)(+) eta) = (0.91 +/- 0.18 (stat) +/- 0.09 (syst))%, constituting the most precise measurements to date.